2009
DOI: 10.1002/pd.2412
|View full text |Cite
|
Sign up to set email alerts
|

Contingent triple‐screening for Down syndrome in the second trimester: a feasibility study in Mainland Chinese population

Abstract: Second-trimester maternal serum contingent triple-screening could be effective and suitable for prenatal care in Mainland China. Governments and Health Agencies of other developing countries may also find this strategy cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…6 , 7 By contrast, our double screening detection rate of 69.6% is higher than rates reported in previous studies examining second trimester double screening in Chinese women (50 to 60%). 4 , 5 The explanation for a seemingly higher detection rate in the present study is unclear, and we are continuing to monitor the results of second trimester double screening for DS to confirm whether the detection rate reported is real or a statistical anomaly. It is worth noting that we found that the second trimester double screening detection rate was markedly lower (56.5%) when the false-positive rate was fixed at 3.0%.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…6 , 7 By contrast, our double screening detection rate of 69.6% is higher than rates reported in previous studies examining second trimester double screening in Chinese women (50 to 60%). 4 , 5 The explanation for a seemingly higher detection rate in the present study is unclear, and we are continuing to monitor the results of second trimester double screening for DS to confirm whether the detection rate reported is real or a statistical anomaly. It is worth noting that we found that the second trimester double screening detection rate was markedly lower (56.5%) when the false-positive rate was fixed at 3.0%.…”
Section: Discussionmentioning
confidence: 53%
“…Serum was isolated at room temperature and stored at 220 8C for measurement of free b-hCG (first and second trimester), PAPP-A (first trimester), and AFP (second trimester) by dissociation-enhanced lanthanide fluorescence immunoassay (DELFIA1235: Perkin Elmer, Waltham, MA). Fetal NT thickness was measured during the first trimester using ultrasound (2)(3)(4)(5). Measurements were made by three trained physicians (note: these physicians were not Fetal Medicine Foundation trained in assessing fetal NT thickness).…”
Section: Sampling and Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All studies except one were cohort studies, among which 85.7% were conducted retrospectively and 4.2% were multicentre. The majority of included studies (92.9%) were conducted in Mainland China.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of prenatal screening and diagnosis is to identify those women at the increased risk for an affected pregnancy and to maximize the options available to them ( 2 ). Maternal serum prenatal screening in second trimester is a screening test that collects the peripheral blood of pregnant women at 15-20 weeks (+ 6 days), combining the age-related risk of maternal for an affected pregnancy with the risks associated with the concentrations of biomarkers ( 3 ). The serum biomarkers involves alpha fetoprotein (AFP), total human chorionic gonadotropin (t-hCG), β-hCG, unconjugated estriol (uE3), free-β-hCG, and Inhibin-A (Inh-A), which have been used in combined forms to produce double (AFP and t-hCG/β-hCG/free β-hCG), triple (AFP, uE3, and t-hCG/β-hCG/free β-hCG) and quadruple (AFP, uE3, Inh-A, and t-hCG/β-hCG/free β-hCG) tests ( 4 ).…”
Section: Introductionmentioning
confidence: 99%